Primer on the physics of the cosmic microwave background - Giovannini Massimo (World Scientific, 2008)
In the last fifteen years, various areas of high energy physics, astrophysics and theoretical physics have converged on the study of cosmology so that any graduate student in these disciplines today needs a reasonably self-contained introduction to the Cosmic Microwave Background (CMB). This book presents the essential theoretical tools necessary to acquire a modern working knowledge of CMB physics. The style of the book, falling somewhere between a monograph and a set of lecture notes, is pedagogical and the author uses the typical approach of theoretical physics to explain the main problems in detail, touching on the main assumptions and derivations of a fascinating subject.
Keywords: Cosmic background radiation